Meningkatkan Hasil Belajar PJOK Materi Bola Voli Menggunakan Permainan 3 on 3 pada Siswa Kelas VIII-3 SMP Negeri 2 Keruak Masa Covid 19 Semester Ganjil Tahun Pelajaran 2021/2022 - Winarko, Hadi (Lembaga Yasin AlSys, 2021)
This study aims to determine whether the 3 on 3 game can improve volleyball bottom passing skills in class VIII-3 students of SMP Negeri 2 Keruak, East Lombok. This research is a classroom action research (classroom action research) which is carried out collaboratively and participatively. The design of this research uses the Kurt Lewin Model in 2 cycles consisting of planning, implementation & observation, and reflection. The research sample includes students of class VIII-3 who found 16 students at SMP Negeri 2 Keruak, East Lombok. The focus of the research is to improve down passing skills. The technique of collecting data is through an action test. The data analysis technique was carried out descriptively, qualitatively and quantitatively. The results showed that the skill of passing under the ball using Game 3 for Class VIII-SMP Negeri 2 Keruak Lombok Timur in East Lombok Regency has increased, namely from the results of the first cycle test obtained as many as 5 students (31.25%) completed learning, and 11 students or 68.75% have not finished studying. Then the results of the second cycle test showed 15 students (93.75%) had completed learning and 1 student or 6.25% had not finished studying. Based on the average results obtained, it can be said that there was an increase of 25.00% in the second cycle from the first cycle. Thus it can be said that using 3 on 3 games can improve the learning process and the ability to pass the ball under the ball grade VIII-3 SMP Negeri 2 Keruak East Lombok.